2019
DOI: 10.1186/s40425-019-0521-4
|View full text |Cite
|
Sign up to set email alerts
|

The IL-1/IL-1 receptor axis and tumor cell released inflammasome adaptor ASC are key regulators of TSLP secretion by cancer associated fibroblasts in pancreatic cancer

Abstract: BackgroundThe thymic stromal lymphopoietin (TSLP), a key cytokine for development of Th2 immunity, is produced by cancer associated fibroblasts (CAFs) in pancreatic cancer where predominant tumor infiltrating Th2 over Th1 cells correlates with reduced patients’ survival. Which cells and molecules are mostly relevant in driving TSLP secretion by CAFs in pancreatic cancer is not defined.MethodsWe performed in vitro, in vivo and ex-vivo analyses. For in vitro studies we used pancreatic cancer cell lines, primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 50 publications
8
74
0
Order By: Relevance
“…In cancer the expression of the two isoforms was evaluated in breast (21) and pancreatic (22) cancers. In breast cancer cells both isoforms were upregulated upon stimulation with IL-1β (21).…”
Section: Tslp Isoforms In Cancermentioning
confidence: 99%
“…In cancer the expression of the two isoforms was evaluated in breast (21) and pancreatic (22) cancers. In breast cancer cells both isoforms were upregulated upon stimulation with IL-1β (21).…”
Section: Tslp Isoforms In Cancermentioning
confidence: 99%
“…A novel role for extracellular ASC released by tumor cells in pancreatic cancer was recently reported (Brunetto et al, 2019). In this study, IL-1α and IL-1β from tumor cells and tumor associated macrophages (TAMs) were key to inducing cancerassociated fibroblasts (CAFs) to secrete the thymic stromal lymphopoietin (TSLP), which in turn drives predominant tumorpromoting Th2 cells, through the activation of resident dendritic cells with Th2 polarizing capability (De Monte et al, 2011;Protti and De Monte, 2012).…”
Section: Asc As Inflammasome Adaptor Moleculementioning
confidence: 85%
“…In pancreatic cancer ASC expression in the tumor, evaluated by immunohistochemistry, was upregulated in over 90% of tumor samples compared with surrounding tissue (Brunetto et al, 2019). Analysis in ASC expression distribution within the tumor showed that, in addition to the expression in tumor cells, ASC was also highly expressed in TAMs in all samples.…”
Section: Asc Expression/aberrant Methylation and Clinical Outcomementioning
confidence: 95%
See 1 more Smart Citation
“…In turn, TSLP was secreted by cancer-associated fibroblasts (CAFs) activated by IL-1α and IL-1β, which are products of cancer cells and tumor cell-conditioned macrophages [ 152 ]. Basophils expressing IL-4 present in the tumor draining lymph nodes of patients with PDAC probably contribute to the stabilization of the Th2 phenotype, since their presence correlates with an increased Th2/Th1 ratio in tumors and poor patient survival [ 153 ]. The Th2-driven responses promoting PDAC also depend on B cells and FcRγ + tumor-associated macrophages (TAMs) expressing Bruton tyrosine kinase (BTK) independent of PI3Kγ.…”
Section: The Role Of Adaptive T Cells In Pdacmentioning
confidence: 99%